Wayfinding signage criteria and ineffectiveness factors towards navigating in Kuala Lumpur International Airport (KLIA2) - Kamal Bahari, Nur Liana; Ibrahim, Nur Hisham; Ahmad Radzi, Mohamad Quzami An-Nuur (Universiti Teknologi MARA, Perak, 2025)
Wayfinding signage is a system that channels information about directions from one area to other locations. Each wayfinding signage has its own criteria to ensure visitors easily understand the messages and follow the navigation. The ineffectiveness of a wayfinding signage system in conveying information has a negative impact on visitors. This review of the literature investigates the important factors that contribute to the failure of wayfinding signage in conveying direction. This includes elements and principle of design (e.g., information, language, fonts, colour, symbol, and sizes). Although the design of the wayfinding signage looks the same, it differs by place. This is when the use of language, terms and information at the airport is not applicable at other places (e.g., airport use term of departure, arrivals, international, domestics, transit). The visitors who came to the airport also have different backgrounds and purpose compared to other places. While there are many guidelines to improve navigation system at airport, many are not investigating the flow of designing the wayfinding signage. Effective wayfinding signage is one that can convey clear information and is able to navigate visitors to the destination in an accurate time.